Get insightful responses to your questions quickly and easily on IDNLearn.com. Join our community to receive prompt and reliable responses to your questions from experienced professionals.
Sagot :
To find the average rate of change of the function [tex]\(f(x) = 2x^2 - x + 1\)[/tex] from [tex]\(x = 1\)[/tex] to [tex]\(x = 3\)[/tex], follow these steps:
### Step 1: Evaluate the function at [tex]\(x = 1\)[/tex]:
First, we need to find the value of the function at [tex]\(x = 1\)[/tex].
[tex]\[ f(1) = 2(1)^2 - 1 + 1 \][/tex]
[tex]\[ f(1) = 2 - 1 + 1 \][/tex]
[tex]\[ f(1) = 2 \][/tex]
### Step 2: Evaluate the function at [tex]\(x = 3\)[/tex]:
Next, we need to find the value of the function at [tex]\(x = 3\)[/tex].
[tex]\[ f(3) = 2(3)^2 - 3 + 1 \][/tex]
[tex]\[ f(3) = 2(9) - 3 + 1 \][/tex]
[tex]\[ f(3) = 18 - 3 + 1 \][/tex]
[tex]\[ f(3) = 16 \][/tex]
### Step 3: Calculate the average rate of change:
The average rate of change of the function over the interval from [tex]\(x = 1\)[/tex] to [tex]\(x = 3\)[/tex] is given by the formula:
[tex]\[ \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]
Substitute [tex]\(x_1 = 1\)[/tex], [tex]\(x_2 = 3\)[/tex], [tex]\(f(x_1) = 2\)[/tex], and [tex]\(f(x_2) = 16\)[/tex]:
[tex]\[ \frac{f(3) - f(1)}{3 - 1} = \frac{16 - 2}{3 - 1} \][/tex]
[tex]\[ \frac{16 - 2}{3 - 1} = \frac{14}{2} \][/tex]
[tex]\[ = 7 \][/tex]
So, the average rate of change of the function [tex]\(f(x) = 2x^2 - x + 1\)[/tex] from [tex]\(x = 1\)[/tex] to [tex]\(x = 3\)[/tex] is [tex]\(7\)[/tex].
### Step 1: Evaluate the function at [tex]\(x = 1\)[/tex]:
First, we need to find the value of the function at [tex]\(x = 1\)[/tex].
[tex]\[ f(1) = 2(1)^2 - 1 + 1 \][/tex]
[tex]\[ f(1) = 2 - 1 + 1 \][/tex]
[tex]\[ f(1) = 2 \][/tex]
### Step 2: Evaluate the function at [tex]\(x = 3\)[/tex]:
Next, we need to find the value of the function at [tex]\(x = 3\)[/tex].
[tex]\[ f(3) = 2(3)^2 - 3 + 1 \][/tex]
[tex]\[ f(3) = 2(9) - 3 + 1 \][/tex]
[tex]\[ f(3) = 18 - 3 + 1 \][/tex]
[tex]\[ f(3) = 16 \][/tex]
### Step 3: Calculate the average rate of change:
The average rate of change of the function over the interval from [tex]\(x = 1\)[/tex] to [tex]\(x = 3\)[/tex] is given by the formula:
[tex]\[ \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]
Substitute [tex]\(x_1 = 1\)[/tex], [tex]\(x_2 = 3\)[/tex], [tex]\(f(x_1) = 2\)[/tex], and [tex]\(f(x_2) = 16\)[/tex]:
[tex]\[ \frac{f(3) - f(1)}{3 - 1} = \frac{16 - 2}{3 - 1} \][/tex]
[tex]\[ \frac{16 - 2}{3 - 1} = \frac{14}{2} \][/tex]
[tex]\[ = 7 \][/tex]
So, the average rate of change of the function [tex]\(f(x) = 2x^2 - x + 1\)[/tex] from [tex]\(x = 1\)[/tex] to [tex]\(x = 3\)[/tex] is [tex]\(7\)[/tex].
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for trusting IDNLearn.com. We’re dedicated to providing accurate answers, so visit us again for more solutions.